Effect of Electron Density on Extreme Ultraviolet Output of a Z-Pinch Xe Discharge Produced Plasma Source - Huang, Bin; Takimoto, Yasuhiro; Watanabe, Masato; Hotta, Eiki (Japanese Journal of Applied Physics, 2011)
The extreme ultraviolet (EUV) source has many applications, including EUV lithography, EUV diagnostics, and so on. Numerous research groups have developed many EUV light sources and studied their characteristics. In this paper, we measured the temporal EUV emission of a Xe discharge produced plasma (DPP) EUV source and later, attempted to clarify the relationship between electron density evolution and EUV emission. The maximum EUV emission occurred at the optimum electron density of about $10^{19}$ cm -3 . A preliminarily discussion of the relationship between EUV radiation and electron density evolution based on these experimental results is presented.